(untitled) (Research, Society and Development, 2022)
The infection caused by SARS-CoV-2 affects the Central Nervous System and, mainly, impairs its sensory functions causing a decrease or loss of smell (hyposmia and anosmia, respectively) and altering the sensitivity of taste (hypogeusia) and even its complete loss (ageusia). The aim of this study is to identify the neuropsychiatric effects caused by SARS-CoV-2. This is an integrative review study, where a search was carried out in the following databases: Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS) and Spanish Bibliographic Index in Sciences of Health (IBECS). The following descriptors were used to search for articles: “coronavirus”, “Neuopsychiatry” and “Consequences”. The inclusion criteria defined for the selection of articles were: articles available online, in full, in Portuguese, English and Spanish, and indexed in the aforementioned databases in the years 2019 to 2022. As exclusion criteria: articles that did not include the theme and repeated studies in the databases. From the initial search with the descriptors and Boolean operator defined, 11 articles were found and of these 4 articles were selected to compose the final sample. In view of the above, we can see that these complications occurred in the most severe cases of the disease, however the most common manifestations were Guillain-Barré syndrome, encephalopathy, encephalitis and psychosis, being common in older patients admitted to an intensive care unit. Considering that the coronavirus is a rather recent pathology, it is necessary to produce more articles to reduce these complications in coronavirus patients.